Comparison of Steroid Hormone Hydroxylations by and Docking to Human Cytochromes P450 3A4 and 3A5 - Toshiro Niwa; Kanae Narita; Ayaka Okamoto; Norie Murayama; Hiroshi Yamazaki (Frontiers Media S.A., 2019)
Purpose: Hydroxylation activity at the 6β-position of steroid hormones (testosterone, progesterone, and cortisol) by human cytochromes P450 (P450 or CYP) 3A4 and CYP3A5 and their molecular docking energy values were compared to understand the catalytic properties of the major forms of human CYP3A, namely, CYP3A4 and CYP3A5. Methods: Testosterone, progesterone, and cortisol 6β-hydroxylation activities of recombinant CYP3A4 and CYP3A5 were determined by liquid chromatography. Docking simulations of these substrates to the heme moiety of reported crystal structures of CYP3A4 (Protein Data Bank code ITQN) and CYP3A5 (6MJM) were conducted. Results: Michaelis constants (Km) for CYP3A5-mediated 6β-hydroxylation of testosterone and progesterone were approximately twice those for CYP3A4, whereas the value for cortisol 6β-hydroxylation mediated by CYP3A5 was similar to the value for that by CYP3A4. Maximal velocities (Vmax) of the three steroid hormones 6β-hydroxylation catalyzed by CYP3A5 were 30%-63% of those by CYP3A4. Thus, Vmax/ Km values of these hormones for CYP3A5 resulted in 22%-31% of those for CYP3A4. The differences in the docking energies between CYP3A4 and CYP3A5 for steroid hormones were slightly correlated to the logarithm of CYP3A5/CYP3A4 ratios for Km values (substrate affinity). Conclusions: The Vmax, rather than Km values, for CYP3A5-mediated 6β-hydroxylation of three steroid hormones were different from those for CYP3A4. Molecular docking simulations could partially explain the differences in the accessibility of substrates to the heme moiety of human CYP3A molecules, resulting in the enzymatic affinity of CYP3A4 and CYP3A5.